Peter Linebaugh, The Magna Carta Manifesto. Liberties and Commons for All (Berkeley: University of California Press, 2008), 368 pp. (2015)
The Magna Carta Manifesto. Liberties and Commons for All (Berkeley: University of California Press, 2008)